Heat transfer by natural convection from a heated square inner cylinder to its elliptical outer enclosure utilizing nanofluids - Bouras, Abdelkrim; Taloub, Djedid; Driss, Zied; Debka, Siham (Zielona Góra: Uniwersytet Zielonogórski)
In this paper a numerical study of natural convection of stationary laminar heat transfers in a horizontal ring between a heated square inner cylinder and a cold elliptical outer cylinder is presented. A Cu-water nanofluid flows through this annular space. Different values of the Rayleigh number and volume fraction of nanoparticles are studied. The system of equations governing the problem was solved numerically by the fluent calculation code based on the finite volume method and on the Boussinesq approximation.
Keywords: natural convection; Rayleigh numbers; nanofluid; volume fraction; square elliptical